Evaluation of various hematological parameters in patients with periodontitis after nonsurgical therapy at different intervals - Srinivasa Tenkasale Siddeshappa; Sonika Nagdeve; Ramreddy Krishnarao Yeltiwar; Humera Parvez; Sushmita Deonani; Vikas Diwan (Wolters Kluwer Medknow Publications, 2016)
Background and Objective: Chronic low-level bacteremia and a systemic inflammatory response have been suggested as a pathogenetic link between periodontal disease and atherosclerosis. The objective of this study is to evaluate the effect of nonsurgical periodontal therapy on various hematological parameters in patients with periodontitis. Materials and Methods: A total of 30 periodontitis patients were selected for the study. Clinical parameters such as plaque index, gingival index, and probing pocket depth were assessed. For each patient, venous blood sample were collected, and the estimation of total leukocyte count (TLC), differential leukocyte count, platelet count, and erythrocyte sedimentation rate (ESR) was carried out. All the clinical and hematological parameters were measured at baseline, 1 week and 2 weeks after nonsurgical periodontal therapy. Results: The study results showed that there was a statistically significant decrease in TLC, ESR, and platelet count at 1 week and 2 weeks following nonsurgical periodontal therapy. Conclusion: In this study, it has been concluded that there is a decrease in the hematological parameters after nonsurgical periodontal therapy, which may also reduce the risk of atherosclerosis formation in the blood vessel and possibly prevent cardiovascular diseases.